The Sahara: Past, present and future - Keenan, Jeremy, 1945- (London (UK): Routledge, 2016)
"This collection examines the Sahara holistically from the earliest (prehistoric) times through the 'historical' period to the present and with political direction into the future. The contributions cover palaeoclimatology, history, archaeology (cultural heritage), social anthropology, sociology, politics and international affairs."--
"This book was previously published as a special issue of the Journal of North African Studies"--Preliminary page
Includes bibliographical references.
Keywords: Antiquities; Civilization; Sahara; Sahara -- Antiquities; Sahara -- Civilization; Sahara; Sahara -- Civilisation; Sahara